GeoGebra Software and Students’ Performance in Coordinate Geometry in Warri South, Delta State, Nigeria - Efor, B. (Journal of Research in Adult and Continuing Education, 2025)
This research investigated the impact of Geogebra software on students’ performance in   Coordinate Geometry in secondary schools within the Warri South, in Delta State, Nigeria.  A quasi-experimental design and descriptive survey approach were adopted with a pretest - posttest control group structure. The population of the study comprised 2,150 Senior Secondary School (SSS 3) Mathematics students from which a sample size of 80 SS 3 Mathematics students was conveniently selected from two schools using purposive sampling technique. Participants were divided into two groups: the experimental group which was taught using Geogebra –assisted instruction, and the control group, which received instruction through the conventional lecture method. The instrument for data collection was the Coordinate Geometry Performance Test (CGPT).  Mean and standard deviation were used to answer the two   research questions while Analysis of Co-variance (ANCOVA) was used to test the two hypotheses formulated for the study at 0.05 level of significance. The findings of this study show that the Geogebra-assisted teaching method is effective in improving students' performance on Coordinate Geometry. The method was shown to be more impactful than the conventional lecture method, fostering greater engagement and understanding among students. Although male students demonstrated slightly higher gains in performance compared to female students, the differences were not statistically significant. The study among others recommended the use of Geogebra – assisted instruction in Mathematics teaching.
Keywords: GeoGebra Software; Students; Performance; Coordinate; Geometry